Novel lipase gene from pseudomonas sp.S5 - Raja Abdul Rahman, Raja Noor Zaliha (2004)

(untitled)
S5 lipase is a solvent stable lipase isolated from Pseudomonas bacterium that can improve enzymatic conversion in high solvent environment, a prerequisite in enzymatic chiral synthesis.